2011
DOI: 10.1002/cjce.20617
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of vertical axis wind turbine: CFD simulations and experimental measurements

Abstract: A system for the conversion of kinetic energy of wind into thermal energy has been developed which can replace relatively expensive electromechanical equipment. The system consists of a vertical axis wind turbine (VAWT) which is coupled with the shaft of a stirred vessel. In the present work, computational fluid dynamic (CFD) simulations have been performed for the flow generated in a stirred tank with disc turbine (DT). The predicted values of the mean axial, radial and tangential velocities along with the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The angular acceleration of Savonius turbine increases, while the rotor moment, M, and inertia of the turbine decrease with increase of the aspect ratio [50]. There are a number of studies for the wind as well as for water as working fluid which reveal that aspect ratio ranging from 1.0 to 2.0 also exhibits good performance of Savonius rotors [39,47,[55][56][57][58][59][60][61][62][63].…”
Section: Effect Of Aspect Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The angular acceleration of Savonius turbine increases, while the rotor moment, M, and inertia of the turbine decrease with increase of the aspect ratio [50]. There are a number of studies for the wind as well as for water as working fluid which reveal that aspect ratio ranging from 1.0 to 2.0 also exhibits good performance of Savonius rotors [39,47,[55][56][57][58][59][60][61][62][63].…”
Section: Effect Of Aspect Ratiomentioning
confidence: 99%
“…Ghatage and Joshi [62] carried out a numerical study to find the optimum twist angle for Savonius rotor having two and three blades with aspect ratio of 2.0. The study resulted in maximum C P ¼ 0.216 at a twist angle of 30°for a two-bladed rotor and maximum C P ¼0.163 at a twist angle of 45°for three blades Savonius rotor.…”
Section: Effect Of Blade Profilementioning
confidence: 99%
“…As a result they have not been interested in the effects of blade thickness, limiting the blades to be thin curves. This approach can be seen in Ghatage and Joshi [12] and Ypma [13], and is not appropriate for this study which considers both lift and drag.…”
Section: Background To Parameterisation Approachesmentioning
confidence: 92%
“…Initial 2D CFD model with less computation cost that 3D model was used to represent the vertical hydrokinetic turbine and the water domain. Based on the review of relevant works [6,[50][51][52], it has been reported that a 2D model is sufficient in revealing the factors that influence the performance and majority of flow physics that surround the vertical-axis hydrokinetic turbine such as hydrofoil profile, N, σ, and D. In the 2D numerical study of this work, the effects from supporting arms were not taken into consideration. Unsteady Reynolds-Averaged Navier-Stokes (RANS) equations were solved using the SIMPLE algorithm for pressure velocity coupling [53][54][55][56].…”
Section: Numerical Model Of the Vertical-axis Hydrokinetic Turbinementioning
confidence: 99%